2004
DOI: 10.3928/0147-7447-20040801-21
|View full text |Cite
|
Sign up to set email alerts
|

Does Graded Reaming Affect the Composition of Reaming Products in Intramedullary Nailing of Long Bones?

Abstract: Reaming products taken during intramedullary nailing were examined to identify possible differences in their composition depending on the reaming percentage. Reaming products were taken from 39 fresh closed tibial and femoral diaphyseal fractures in patients with an average age of 29 years. According to histology, reaming products mainly consisted of bone trabecular viable or nonviable, and bone marrow stroma. A statistically significant reverse correlation exists between viable bone mass percentage and reamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This is because of its availability and biomechanical advantage. For several authors, nailing appears to be the gold standard method for the treatment of aseptic femoral non-union [17,18]. Indeed, the reaming of the femoral canal and its local biological effect, as well as the mechanical advantages of placing a larger and stronger centromedullary nail, have been proven [19].…”
Section: Discussionmentioning
confidence: 99%
“…This is because of its availability and biomechanical advantage. For several authors, nailing appears to be the gold standard method for the treatment of aseptic femoral non-union [17,18]. Indeed, the reaming of the femoral canal and its local biological effect, as well as the mechanical advantages of placing a larger and stronger centromedullary nail, have been proven [19].…”
Section: Discussionmentioning
confidence: 99%
“…About possible treatments for PSA, Kouzelis et al have demonstrated that reaming the femoral canal has an important osteo-inductive biological effect due to reaming debris, which acts as an autologous endogenous graft [22]. Another possible treatment is an internal fixation with plate and screws, a more invasive surgery which allows excision of the fibrous tissue at the PSA focus, direct visualisation of the fracture site, and correction of rotation and mechanical axis [23].…”
Section: Discussionmentioning
confidence: 99%